The extraordinary radio galaxy MRC B1221-423: probing deeper at radio and optical wavelengths - Johnston, H; Broderick, J; Cotter, G; Morganti, R; Hunstead, R (2010)
We present optical spectra and high-resolution multiwavelength radio observations of the compact steep-spectrum radio source MRC B1221-423 (z = 0.1706). MRC B1221-423 is a very young (∼105 yr), powerful radio source which is undergoing a tidal interaction with a companion galaxy. We find strong evidence of interaction between the active galactic nucleus (AGN) and its environment. The radio morphology is highly distorted, showing a dramatic interaction between the radio jet and the host galaxy, with the jet being turned almost back on itself. H i observations show strong absorption against the nucleus at an infall velocity of ∼250 km s-1 compared to the stellar velocity, as well as a second, broader component which may represent gas falling into the nucleus. Optical spectra show that star formation is taking place across the whole system. Broad optical emission lines in the nucleus show evidence of outflow. Our observations confirm that MRC B1221-423 is a young radio source in a gas-rich nuclear environment, and that there was a time delay of a few times 100 Myr between the onset of star formation and the triggering of the AGN. © 2010 The Authors. Journal compilation © 2010 RAS.